Entrepreneurial Orientation on Food and Beverage SMEs’ Performance : The Role of Competitive Advantage and Innovation - Sukmamedian, Haufi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to see the effect of entrepreneurial orientation, innovation, and competitive advantage on the performance of the culinary sector SMEs in Bogor, West Java. The research was conducted in the culinary industry sector in the city of Bogor. 270 questionnaires were distributed, but 161 were returned so that the sample in this study was 161 respondents. The research was conducted by using quantitative methods. The data analysis used was path analysis with Amos version 23 software. The results showed that there was a positive and significant influence between entrepreneurial orientation, innovation, and competitive advantage on performance. Entrepreneurial orientation has an influence on innovation and competitive advantage. Then, innovation has an effect on competitive advantage. The results also show that innovation and competitive advantage can mediate the effect of entrepreneurial orientation on performance. The recommendation of this research is to increase the competitiveness of the culinary industry by increasing the ability of innovation and entrepreneurial orientation.